Localizing Global Goals: Bekasi’s Paradiplomacy in Vocational Education Cooperation with Japan - Naeli FITRIA (International Journal of Environmental, Sustainability, and Social Science, 2025)
Indonesia-Japan collaboration on vocational education has been a strategic step toward increased labor demand and youth employment opportunities. Local governments are effective facilitators of such partnerships by connecting schools, industries, and foreign partners. This is a real-life example of the Indonesian city of Bekasi in West Java where the local government facilitated the partnership of SMK Mitra Industri MM2100 and Japanese partners. Through partnerships with Japanese industries at the MM2100 Industrial Estate and Japanese training centers, students are furnished with industry-specific curricula, training of their technical expertise, and internship placements at home and abroad. This partnership not only endows students with hands-on experience of engineering and manufacturing but also improves their intercultural ability, linguistic skills, and adaptation to work environments worldwide. Japan brings their expertise by donating training modules, professional mentorship, and internship placements while the government of Bekasi facilitates alignment of policy, provision of funds and coordination with local industries. This partnership is a realization of Indonesia's vocational revitalization program of closing education and labor market disparities. It is more fundamentally designed to generate socioeconomic results like youth employment minimization and local industry competitiveness enhancement. Also, it contributes toward Sustainable Development Goals (SDGs), particularly Goal 4 (quality education), Goal 8 (decent work and economic growth), and Goal 17 (partnership for the goals). This example of partnership by Bekasi and Japan is evidence of the contribution of multi-level governance of education cooperation and can inspire other regions seeking strong foreign partnership-based human capital development.